Coassembly of elastomeric microfibers and silver nanowires for fabricating ultra-stretchable microtextiles with weakly and tunable negative permittivity. (26th May 2022) - Zhou, Yunlei; Qu, Yunpeng; Yin, Liting; Cheng, Wenna; Huang, Yongan; Fan, Runhua
Abstract: In this work, a type of unique flexible and ultra-stretchable microtextiles was fabricated by coassembly of Ag nanowires (AgNWs) and thermoplastic polyurethane (TPU) microfibers. The microtexiles show tunable and weakly negative permittivity at a low filler content of 1.0–2.4 wt%. The resonance-induced negative permittivity observed in the AgNW/TPU microtextiles below the percolation threshold ( f c ) is attributed to the electric dipole moment of the isolated AgNWs, and this phenomenon can be explained by the Lorentz model. When the AgNW content exceeds the f c, the low-frequency collective plasma oscillation of the AgNW networks in the composites triggers the tunable plasma-type negative permittivity, which agrees with the Drude model. Additionally, the inductive character of the composites was assessed with the reactance spectra. The as-prepared Ag/TPU microtextiles could be a good candidate for the applications of garment integrated electronic, novel sensors, electromagnetic cloaking, and wearable electronic devices. Graphical abstract: Image 1